A Human Rights Approach to Consumer Safety and Well-being: The Balance Between Deterring Violations of Consumer Rights and Promoting Free Trade - Choi, Eun Hae (Grace) (Auckland University of Technology, 2021)
As the global demand for free trade continues to expand, the matter of consumer safety and well-being must no longer be regarded as a ‘luxury’ but to be essential to maintain human dignity. Since an overwhelming majority of people, in essence, become consumers from time to time, their rights must be protected regardless of where they live or what their socioeconomic status may be. In that respect, this paper aims to stress the need for recognising consumer safety and its relevant rights as human rights. In establishing this argument, the detailed discussion of Korea’s humidifier disinfectant products case (“HD case”) is essential. In addressing the HD case in detail, this paper has attempted to demonstrate how the discrepancies in domestic laws may create a system-generated risk that can eventually lead to compromise the safety of consumers. That is to say, if the Korean legal system could have successfully eliminated such risks by implementing adequate product-safety-proving requirements like the EU’s, the result of the HD case may have turned out to be different. Likewise, under the current New Zealand law, it is evident that even in a situation where a company’s failure to protect consumers can be established, it is often difficult to hold a company liable. In enforcing consumer protection as a matter of international human rights law, this paper shows that there is a clear need for controlling or regulating multinational actors by implementing appropriate non-voluntary legal mechanisms. The discussion on the possible balancing act between deterring violations of consumer rights and promoting free trade is another primary focus of this paper. Based on the relevant discussions and analyses, a conclusion was reached that as a way of balancing the protection of consumer rights and the promotion of the free trade relationships, it is conceivable to choose a ‘soft-law-based’ approach by applying Hopkins and McNeill’s cultural filter theory. Alternatively, Benöhr’s capability approach suggests that taking a method of enhancing the necessary capabilities of consumers could also make it possible to find a sensible balance between protecting consumer rights and promoting free trade. Yet, in order for such a ‘soft-law-based’ approach to be pragmatic, the chosen approach must be accompanied by an obligation to implement controlling or regulating mechanisms. In other words, trading parties must also commit to play their part in securing consumer safety on the ‘harder’ side of the law. On that basis, therelevant recommendations may include introducing a social clause and establishing a Joint Committee in the appropriate chapter of an international trade agreement.
Keywords: Corporate & Commercial; Criminal Law; White-Collar Crime; Corporate Regulations; Human Rights; International Court of Justice; Consumer Rights; Consumer Protection; Product Safety; Fair Trading; International Trade; Free Trade Agreement